Child Rights Advocacy Efforts and Nigerian Film Industry: An Analysis of Select Movies - ONYEJELEM, Timothy Ekeledirichukwu (International Journal of Global Sustainable Research, 2024)
The Nigerian film industry, particularly Nollywood, has a significant impact on societal attitudes and norms, but there is a lack of comprehensive studies on how it promotes children's rights. This study aimed to examine the intersection of child rights advocacy efforts in Nigeria and the Nigerian movie industry, focusing on the portrayal of child rights issues in films. The research, which used Social Representation Theory, found that child trafficking, child labor, child battering, child molestation, child rape, child marriage, and deprivation of education were prominent issues depicted in the films. The study also recommended increased collaboration between child rights advocacy organizations like UNICEF and Nigerian filmmakers to ensure accurate and impactful messages about child rights are portrayed in movies.